Dercum's Disease: A Case Report of a Patient Having Both Type 1 and Type 2 Dercum's Disease - Cameron Moattari; Richard A. Giovane; Stephanie DiGiovanni Kinsely (Hindawi Limited, 2020)
Dercum's disease, or adiposis dolorosa, is a rare disorder which consists of multiple, painful lipomas within the subcutaneous tissue and has a distribution mainly in the abdomen and extremities. Dercum's disease can be defined as in combination with chronic painful adipose tissue. Although the etiology of Dercum's disease is not clear, it is thought to be a combination of a neurological and endocrine disorder. Treatment for this disease is centered at managing pain. Although there is no standard of care for managing pain, there are different pain management regimes that are promising.